2004
DOI: 10.1002/chir.20010
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition based on enantioselective interactions of propranolol enantiomers with cyclosophoraoses isolated from Rhizobium meliloti

Abstract: Cyclosophoraoses isolated from Rhizobium meliloti, as an NMR chiral shift agent, were used to discriminate propranolol enantiomers. Continuous variation plot made from the complex of cyclosophoraoses with propranolol showed that the diastereomeric complex had predominantly 1:1 stoichiometry through UV spectroscopic analysis. The chiral recognition of propranolol enantiomers by cyclosophoraoses was investigated through the determination of binding constant based on the (13)C NMR chemical shift changes. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It has been recently reported that Cys act as complexing agents with a variety of hydrophobic guest molecules, enhancing their solubility in water . In addition, because of their chiral selectivity, Cys molecules are widely used as chiral additives in the separation of enantiomers by capillary electrophoresis method and as chiral stationary phase (CSP) in high‐performance liquid chromatography (HPLC) . Recently, modified cyclodextrins (cyclic α‐1,4‐glycans, CDs) have also been efficiently employed as CSPs in HPLC .…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently reported that Cys act as complexing agents with a variety of hydrophobic guest molecules, enhancing their solubility in water . In addition, because of their chiral selectivity, Cys molecules are widely used as chiral additives in the separation of enantiomers by capillary electrophoresis method and as chiral stationary phase (CSP) in high‐performance liquid chromatography (HPLC) . Recently, modified cyclodextrins (cyclic α‐1,4‐glycans, CDs) have also been efficiently employed as CSPs in HPLC .…”
Section: Methodsmentioning
confidence: 99%
“…Cyclic b-(1,2) glucans (family I) are used in the separation of enantiomers, and the first study reported the chiral discrimination ability on Nacetylphenylalanine, catechin and propranolol using NMR spectroscopy [109,110]. In the enantiomeric interactions, C1 and C2 carbons composed of b glycosidic linkages actively participated.…”
Section: Chirotechnologymentioning
confidence: 99%
“…This complexation ability has been taken advantage not only of differentiating one enantiomer from another [24,25] but also of quanti- tatively determining flavonoids [22,23]. However, some carbohydrates derived from microorganisms having unique complex-forming activity other than cyclodextrins for certain reactions have been recently introduced [29,[32][33][34][35], where they functioned as catalysts or chiral selectors for various chemicals. Succinoglycan monomers isolated from a soil microorganism, R. meliloti 2011 are divided into three different structures, M1, M2 and M3, depending on the number of substituent, succinyl group, as shown in Fig.…”
Section: The Redox Reaction Of Quercetin On the Mwnts-based Gce Modifmentioning
confidence: 99%